2022
DOI: 10.3389/fcimb.2022.986314
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA profiling of Plasmodium vivax-infected hepatocytes reveals parasite- and host- specific transcriptomic signatures and therapeutic targets

Abstract: The resilience of Plasmodium vivax, the most widely-distributed malaria-causing parasite in humans, is attributed to its ability to produce dormant liver forms known as hypnozoites, which can activate weeks, months, or even years after an initial mosquito bite. The factors underlying hypnozoite formation and activation are poorly understood, as is the parasite’s influence on the host hepatocyte. Here, we shed light on transcriptome-wide signatures of both the parasite and the infected host cell by sequencing o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 127 publications
1
28
1
Order By: Relevance
“…1 ). Moreover, the study by Ruberto et al [ 27 ] reported opposite modulations of host pathways (e.g., upregulations of host genes associated with translation and oxidative phosphorylation) in hepatocytes infected with P. vivax , which is in apparent disagreement with our results, as well as with results from others [ 23 , 26 ]. Thus, beyond the impact of malaria- and host-species specific variations, current results suggest that the hepatocyte response to infection is highly dynamic or influenced by technical aspects (e.g., the source of human hepatocytes).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1 ). Moreover, the study by Ruberto et al [ 27 ] reported opposite modulations of host pathways (e.g., upregulations of host genes associated with translation and oxidative phosphorylation) in hepatocytes infected with P. vivax , which is in apparent disagreement with our results, as well as with results from others [ 23 , 26 ]. Thus, beyond the impact of malaria- and host-species specific variations, current results suggest that the hepatocyte response to infection is highly dynamic or influenced by technical aspects (e.g., the source of human hepatocytes).…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies reported the host transcriptional profile of human hepatocytes infected with P. vivax [ 26 , 27 ]. Interestingly, Mancio-Silva et al [ 26 ] found that the late phase of the P. vivax liver stage is associated with the downregulation of liver-specific functions as well as translation, as observed for P. cynomolgi - and P. berghei -infected hepatocytes (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The hit MS-0735, an analog of our previously reported hypnozonticidal hit MMV018983 ( 13 ), is a ribonucleotide-reductase (RNR) inhibitor used as an antiviral. Needed for producing deoxyribonucleosides for DNA synthesis, RNR is a peculiar mechanism for nonreplicating hypnozoites, however, it has been reported that RNR is critical for DNA damage repair ( 38 ) and is expressed in P. vivax liver schizonts and hypnozoites ( 19 ). Ongoing efforts to make available disruptive methods for studying P. vivax , including genetic manipulation and in vivo models for relapse, will enable further validation of these leads and a more comprehensive understanding of the mechanisms of hypnozoite quiescence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cancer drug poziotinib inhibits HER2, a tyrosine protein kinase associated with the downregulation of apoptosis and metastasis (37). As we recently reported that host apoptotic pathways are downregulated in P. vivax-infected hepatocytes, poziotinib could act by increasing apoptotic pathways in infected host cells (19). The hit MS-0735, an analog of our previously reported hypnozonticidal hit MMV018983 (13), is a ribonucleotide-reductase (RNR) inhibitor used as an antiviral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation